2019
DOI: 10.1038/s41389-019-0143-1
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of 14-3-3ζ links YAP transcriptional activation to hypoxic glycolysis for tumorigenesis

Abstract: Hypoxic microenvironment deregulates metabolic homeostasis in cancer cells albeit the underlying mechanisms involved in this process remain hitherto enigmatic. 14-3-3ζ/Yes-associated protein (YAP) axis plays a principal role in malignant transformation and tumor development. Here, we report that hypoxia disassembles 14-3-3ζ from YAP and thereby promotes YAP nuclear localization mediated by ERK2, which directly binds to the D-site of mitogen-activated protein kinase (MAPK) docking domain in 14-3-3ζ Leu98/100 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 47 publications
(56 reference statements)
0
45
0
Order By: Relevance
“…Interestingly, YAP cooperates with other transcription regulators to control many genes related to glycolysis. For example, YAP interacts with HIF1α and regulates the transcription of various genes involved in aerobic glycolysis such as GLUT1, HK2, ALDOA, LDHA, and PKM2 (129,130). The YAP-TEAD complex interacts with p65 and upregulates the transcription of HK2 (131).…”
Section: The Role Of Yap/taz In Glucose Metabolismmentioning
confidence: 99%
“…Interestingly, YAP cooperates with other transcription regulators to control many genes related to glycolysis. For example, YAP interacts with HIF1α and regulates the transcription of various genes involved in aerobic glycolysis such as GLUT1, HK2, ALDOA, LDHA, and PKM2 (129,130). The YAP-TEAD complex interacts with p65 and upregulates the transcription of HK2 (131).…”
Section: The Role Of Yap/taz In Glucose Metabolismmentioning
confidence: 99%
“…Hypoxia-inducible factor 1α (HIF1α) and c-Myc as the main transcription factors regulating glycolysis [62,63] were also found to be associated with YAP and to regulate the expression of key glycolysis enzymes and glycolysis. As studies reported, YAP binds to these transcription factors in the nucleus and regulates cell glycolysis [62,[64][65][66]. Altogether, Hippo signaling can regulate cell glucose metabolism in a variety of ways.…”
Section: Regulation Of Metabolism By Hippo Signalingmentioning
confidence: 87%
“…Furthermore, they are also involved in biological processes such as apoptosis [30], autophagy [31], EMT [32] and even the Warburg Effect [33]. For instance, in a hypoxic microenvironment, a noticeable link has been found between YAP transcriptional activation and hypoxic glycolysis governed by the ERK2-dependent 14-3-3ζ Ser37 [34]. The phosphorylation for malignant progression in MEK1/2 activates human ERK1/2 by rst catalysing the phosphorylation of Y204/187 and then T202/185, both residues of which occur within the activation segment.…”
Section: Discussionmentioning
confidence: 99%